[Letter from Featherstonhaugh, Conway, Wiley & Clyne, LLP to Walter Woodson] (Tufts Archival Research Center, 2007)
Letter from Featherstonhaugh, Conway, Wiley & Clyne, LLP to Walter Woodson. Expresses pleasure in working with Woodson and the Tobacco Institute Labor Management Committee (TILMC). Proposes fee for representing TILMC for the year. Announces plan to register as lobbyists for the TILMC if proposal is accepted.